Role of bone marrow adipocytes in bone metastasis development and progression: a systematic review - Salamanna, F.; Contartese, D.; Errani, C.; Sartori, M.; Borsari, V.; Giavaresi, G. (Frontiers in Endocrinology, 2023)
Purpose: Bone marrow adipocytes (BMAs) are the most plentiful cells in bone marrow and function as an endocrine organ by producing fatty acids, cytokines, and adipokines. Consequently, BMAs can interact with tumor cells, influencing both tumor growth and the onset and progression of bone metastasis. This review aims to systematically evaluate the role of BMAs in the development and progression of bone metastasis. Methods: A comprehensive search was conducted on PubMed, Web of Science and Scopus electronic databases, following the PRISMA statement standards, to identify studies published from March 2013 to June 2023. Two independent reviewers assessed and screened the literature, extracted the data, and evaluated the quality of the studies. The body of evidence was evaluated and graded using the ROBINS-I tool for non-randomized studies of interventions and to the Systematic Review Centre for Laboratory Animal Experimentation tool for in vivo studies. The results were synthesized using descriptive methods. Results: A The search yielded a total of 463 studies, of which 17 studies that were finally included in the final analysis, including 15 preclinical studies and 2 non-randomized clinical studies. Analysis of preclinical studies revealed that BMAs play a significant role in bone metastasis, particularly in prostate cancer followed by breast and malignant melanoma cancers. BMAs primarily influence cancer cells by inducing a glycolytic phenotype and releasing or up-regulating soluble factors, chemokines, cytokines, adipokines, tumor-derived fatty acid binding proteins, and member of the nuclear receptor superfamily, such as chemokine (C-C motif) ligand 7, C-X-C Motif Chemokine Ligand (CXCL)1, CXCL2, interleukin (IL)1β, IL6, FABP4, proliferator-activated receptor γ. These factors also contribute to adipocyte lipolysis and regulate a pro-inflammatory phenotype in BMAs. However, the number of clinical studies is limited, and definitive conclusions cannot be drawn. Conclusion: The preclinical studies reviewed indicate that BMAs may play a crucial role in bone metastasis in prostate, breast and malignant melanoma cancers. Nevertheless, further preclinical and clinical studies are needed to better understand the complex role and relationship between BMAs and cancer cells in the bone microenvironment. Targeting BMAs in combination with standard treatments holds promise as a potential therapeutic strategy for bone metastasis.